Hierarchical Assembly and Sensing Activity of Patterned Graphene-Hamilton Receptor Nanostructures - Bao, Lipiao; Zhao, Baolin; Ali, Muhammad; Assebban, M'hamed; Yang, Bowen; Kohring, Malte; Ryndyk, Dmitry A.; Heine, Thomas; Weber, Heiko B.; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2022)

Hypervalent Iodine Compounds as Versatile Reagents for Extremely Efficient and Reversible Patterning of Graphene with Nanoscale Precision - Bao, Lipiao; Zhao, Baolin; Yang, Bowen; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2021)
Rational patterning and tailoring of graphene relies on the disclosure of suitable reagents for structuring the target functionalities on the 2D-carbon network. Here, a series of hypervalent iodine compounds, namely, 1-chloro-1,2-benziodoxol-3(1H)-one, 1,3-dihydro-1-hydroxy-3,3-dimethyl-1,2-benziodoxole, and 3,3-dimethyl-1-(trifluoromethyl)-1,2-benziodoxole is reported to be extremely efficient for a diversified graphene patterning. The decomposition of these compounds generates highly reactive Cl, OH, and CF3 radicals exclusively in the irradiated areas, which subsequently attach onto the graphene leading to locally controlled chlorination, hydroxylation, and trifluoromethylation, respectively. This is the first realization of a patterned hydroxylation of graphene, and the degrees of functionalization of the patterned chlorination and trifluoromethylation are both unprecedented. The usage of these mild reagents here is reasonably facile compared to the reported methods using hazardous Cl-2 or ICl and allows for sophisticated pattern designs with nanoscale precision, promising for arbitrary nanomanipulation of graphene's properties like hydrophilicity and conductivity by the three distinct functionalities (Cl, OH, and CF3). Moreover, the attachment of functional entities to these highly functionalized graphene nanoarchitectures is fully reversible upon thermal annealing, enabling a full writing/storing/reading/erasing control over the chemical information stored within graphene. This work provides an exciting clue for target 2D functionalization and modulation of graphene by using suitable hypervalent iodine compounds.
CRIS-Team WoS Importer:2021-07-09

Spatially Resolved Janus Patterning of Graphene by Direct Laser Writing - Al-Fogra, Sabrin; Yang, Bowen; Jurkiewicz, Lisa; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Journal of the American Chemical Society, 2022)
Covalently patterned Janus-functionalized graphene featuring a spatially defined asymmetric bifacial addend binding motif remains a challenging synthetic target. Here, a facile and universal laser writing approach for a one-step covalent Janus patterning of graphene is reported, leading to the formation of up to now elusive graphene architectures, solely consisting of antaratopically functionalized superlattices. The structurally defined covalent functionalization procedure is based on laser-triggered concurrent photolysis of two different photosensitizers situated on both sides of the graphene plane, generating radicals and subsequent addend binding in the laser-irradiated areas only. Careful structure analysis was performed by Raman spectroscopy and Kelvin probe force microscopy. In terms of the advantages of our newly established concept, including a simple/easy-to-operate patterning procedure, arbitrary pattern availability, and a high degree of addend binding, an easy access to tailor-designed Janus-functionalized graphene devices with spatially resolved functional entities can be envisaged.
CRIS-Team Scopus Importer:2022-11-04

Synergistic Combination of Reductive Covalent Functionalization and Atomic Layer Deposition—Towards Spatially Defined Graphene-Organic-Inorganic Heterostructures - Liu, Xin; Yang, Bowen; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; Bachmann, Julien; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Angewandte Chemie International Edition, 2023)
Three-dimensionally (3D) well-ordered and highly integrated graphene hybrid architectures are considered to be next-generation multifunctional graphene materials but still remain elusive. Here, we report the first realization of unprecedented 3D-patterned graphene nano-ensembles composed of a graphene monolayer, a tailor-made structured organophenyl layer, and three metal oxide films, providing the first example of such a hybrid nano-architecture. These spatially resolved and hierarchically structured quinary hybrids are generated via a two-dimensional (2D)-functionalization-mediated atomic layer deposition growth process, involving an initial lateral molecular programming of the graphene lattice via lithography-assisted 2D functionalization and a subsequent stepwise molecular assembly in these regions in the z-direction. Our breakthrough lays the foundation for the construction of emerging 3D-patterned graphene heterostructures.
CRIS-Team Scopus Importer:2023-10-27
Keywords: 3D Patterning; Atomic Layer Deposition; Graphene Chemistry; Heteroarchitectures; Molecular Assembly